Investigation of Oligoclonal IgG Bands in Tear Fluid of Multiple Sclerosis Patients - Hümmert, Martin W.; Wurster, Ulrich; Bönig, Lena; Schwenkenbecher, Philipp; Sühs, Kurt-Wolfram; Alvermann, Sascha; Gingele, Stefan; Skripuletz, Thomas; Stangel, Martin (Frontiers in Immunology, 2019)
Background: Oligoclonal IgG bands (OCB) in the cerebrospinal fluid (CSF) represent a typical marker for inflammation in multiple sclerosis (MS) patients and have a predictive and diagnostic value in patients with a first suspected demyelinating event. The detection in tears remains controversial but some reports suggested a replacement of CSF analysis by OCB detection in tears. We aimed to investigate the value of OCB detection in tears systematically in patients with MS. Methods: Tears of 45 patients with suspected or diagnosed MS were collected with Schirmer filter paper strips. Tear IgG was purified by affinity chromatography with protein G. After isoelectric focusing in polyacrylamide gels OCB detection was performed with direct silver staining. Paired triplets of CSF, serum, and tears were analyzed. For comparison purposes we additionally used other tear collection methods (flush procedure and plastic capillary tubes) or detection techniques (Western blotting). Results: IgG collection in tears was most reliable by using Schirmer strips. 11 patients had to be excluded due to insufficient sample material. Tear specific proteins that interfered with OCB detection were successfully eliminated by IgG purification. The concordance of OCB in tears and CSF of all investigated MS patients was 41% with a high rate of only marginal pattern in tears. 3 patients demonstrated restricted bands in tears, neither detectable in CSF nor serum. Conclusion: Due to the limited concordance, high rate of samples with insufficient material, and the unknown origin of tear IgG we cannot recommend that tear OCB detection may replace CSF OCB detection in MS patients. The detection of unique OCB in tears might offer new insights in ophthalmological diseases.